Binge eating disorder: epidemiological, clinical, pathophysiological, and treatment aspects - E. G. Starostina; M. V. Ananyan (Сахарный диабет, 2024)
Binge eating disorder (BED) is the most prevalent type of eating disorders encountered in endocrinological practice, with 5 to 66% of obesity patients seeking for losing weight, 10 to 25% of patients with Type 2 diabetes mellitus, and above 70% of Type 2 patients with morbid obesity having BED. BED can seriously challenge the treatment for Type 2 diabetes and obesity, but remains underdiagnosed and undertreated in most cases. The review discussed diagnostic criteria of BED and their evolution during the last three decades, as well as neurochemical, genetic, and psychological components of its pathophysiology and potential role of BED as a new risk factor for Type 2 diabetes. We have also analyzed medical treatments available for an endocrinologist, including potential use of agonists of glucagone-like peptide 1 receptors.